Membangun National Branding Image Kepulauan Riau Sebagai Poros Maritim Dunia - Poti, Jamhur (Jurnal Ilmu Administrasi Negara (JUAN), 2016)
Nation Branding serves to build, develop, and maintain a good image of a country. This theory is based on the results of observations and studies that claim that a countrys success in competing in the global market is strongly influenced by the countrys brand image. In fact, it is said that the branding and image of a country coupled with a commensurate transfer of the image to the products produced as important as the products produced by the state itself. To build a maritime shaft Indonesia, of course, all potential make it happen. Including deployed for the construction of national branding are integrated in a unified concept, the which raised or highlight the potential of marine and maritime aspects. National branding of course need to be integrated with other brandings the creation for similar interests. Likewise city branding of each of the cities, especially coastal cities, should refer to the main theme of national branding, the marine and maritime sectors. With the unified theme of branding will be forming a strong image. And more memorable. The need for national branding as the promotion of marine and maritime vision of Indonesia roomates in turn attract more investors, tourists, and enhance the value and competitiveness of trade with other countries. The idea to make-the Riau Islands as Indonesia and the axle shafts maritime world, should be supported by policies and decisions seriously. Strategic geographical location between South China Sea and the Malacca strait with natural resources potential. Riau Islands Province, it is possible to become a center of economic growth in the Republic of Indonesia in the future. Riau Islands directly dealing with neighboring Singapore and Malaysia. Besides, It also became connectivity or connect between one region and another. In addition to sea lanes, some areas need to be connected to the airport. Now is the time Indonesia needs to build a national branding according to the vision of marine and maritime government aim to achieve. Not only touched the tourism sector alone, but also need to reflect the potential of natural and marine industries are extensive. So that not only attract tourists to visit, but also able to invite the interest of investors to invest in the marine and maritime sectors